2023
DOI: 10.1039/d2su00078d
|View full text |Cite
|
Sign up to set email alerts
|

Recycling post-consumer PLA into acrylic acid or lactide using phosphonium ionic liquids

Abstract: Chemical recycling of polymer waste to the original monomer (CRM) forms an important concept for a circular plastic economy. For poly(lactic acid) (PLA) this is often neglected as a result...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…46 In a recent paper, the depolymerisation of PLA into reusable lactide and acrylic acid was reported using ionic liquids and an acidic co-catalyst. 47 Having established ZnO to be an effective heterogeneous catalyst for the hydrolysis reaction of PLA, we then investigated the hydrolysis of a more complex co-polymer, namely polyethylene terephthalate (PET). PET is one of the most common synthetic organic polymers.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…46 In a recent paper, the depolymerisation of PLA into reusable lactide and acrylic acid was reported using ionic liquids and an acidic co-catalyst. 47 Having established ZnO to be an effective heterogeneous catalyst for the hydrolysis reaction of PLA, we then investigated the hydrolysis of a more complex co-polymer, namely polyethylene terephthalate (PET). PET is one of the most common synthetic organic polymers.…”
Section: Resultsmentioning
confidence: 99%
“…46 In a recent paper, the depolymerisation of PLA into reusable lactide and acrylic acid was reported using ionic liquids and an acidic co-catalyst. 47…”
Section: Resultsmentioning
confidence: 99%
“…[39][40][41][42][43][44][45][46][47][48][49] The portfolio of investigated catalysts includes simple inorganic compounds, [46][47][48][49][50] organic compounds, 44,45 and ionic liquids. [38][39][40][41]51,52 It seems obvious that this set should include metal coordination compounds that are active in the ROP process of lactides, but this aspect has only emerged in recent years, generally for magnesium and zinc compounds. 32,[53][54][55][56][57][58][59][60][61] The first example was a homoleptic zinc aminophenolate, where we demonstrated that this catalyst exhibits bifunctional characteristics, being active in both the lactide polymerization process and PLA degradation, although the latter process is significantly less efficient.…”
Section: Introductionmentioning
confidence: 99%